A scoping review examining patient experience and what matters to people experiencing homelessness when seeking healthcare - Jean-Philippe Miller; Jennie Hutton; Claire Doherty; Shannen Vallesi; Jane Currie; Katrina Rushworth; Matthew Larkin; Matthew Scott; James Morrow; Lisa Wood (BMC, 2024)
Abstract Background Homelessness is associated with significant health disparities. Conventional health services often fail to address the unique needs and lived experience of homeless individuals and fail to include participatory design when planning health services. This scoping review aimed to examine areas of patient experience that are most frequently reported by people experiencing homelessness when seeking and receiving healthcare, and to identify existing surveys used to measure patient experience for this cohort. Methods A scoping review was undertaken reported according to the PRISMA-ScR 2020 Statement. Databases were searched on 1 December 2022: MEDLINE, EMBASE, APA PsychINFO and CINAHL. Included studies focused on people experiencing homelessness, healthcare services and patient experience, primary research, published in English from 2010. Qualitative papers and findings were extracted and synthesized against a modified framework based on the National Institute for Health and Care Excellence guidelines for care for people experiencing homelessness, the Institute of Medicine Framework and Lachman's multidimensional quality model. People with lived experience of homelessness were employed as part of the research team. Results Thirty-two studies were included. Of these, 22 were qualitative, seven quantitative and three mixed methods, from the United States of America (n = 17), United Kingdom (n = 5), Australia (n = 5) and Canada (n = 4). Health services ranged from primary healthcare to outpatient management, acute care, emergency care and hospital based healthcare. In qualitative papers, the domains of 'accessible and timely', 'person-centred', and values of 'dignity and respect' and 'kindness with compassion' were most prevalent. Among the three patient experience surveys identified, 'accessible and timely' and 'person-centred' were the most frequent domains. The least frequently highlighted domains and values were 'equitable' and 'holistic'. No questions addressed the 'safety' domain. Conclusions The Primary Care Quality-Homeless questionnaire best reflected the priorities for healthcare provision that were highlighted in the qualitative studies of people experiencing homelessness. The most frequently cited domains and values that people experiencing homelessness expressed as important when seeking healthcare were reflected in each of the three survey tools to varying degrees. Findings suggest that the principles of 'Kindness and compassion' require further emphasis when seeking feedback on healthcare experiences and the domains of 'safety', 'equitable', and 'efficiency' are not adequately represented in existing patient experience surveys.